What is Noise Sensitivity? - David Welch; Kim N Dirks; Daniel Shepherd; Jessica Ong (Noise and Health, 2022)
Background: Noise sensitivity moderates the association between environmental noise exposure and annoyance and health outcomes. Methods: In normally hearing adults, we measured noise sensitivity in three ways: using the noise sensitivity questionnaire, a 3-point self-rating, and the loudness discomfort level (LDL; mean reported discomfort level for tone bursts). We then presented recordings of a 15-second 80 dBLAeq aeroplane overflight and participants rated the annoyance and loudness they experienced. Results: The three measures of noise sensitivity were not well correlated with each other, and only the overall LDL was associated with the ratings of loudness and annoyance in response to the aeroplane sounds. Conclusions: This implies that our current measures of noise sensitivity may only capture parts of the underlying construct, and therefore underestimate effects due to it on the association between environmental noise and annoyance and health outcomes. We developed a theoretical model to describe the set of factors that may influence a person’s sensitivity to noise and propose that interaction between the systems described is the basis for noise sensitivity. This paradigm alters the focus of noise research from the annoyance caused by the sound, to the sensitization to noise that may occur as a result of the interplay of many factors. We hope that our model will allow research to explore the sensitizing factors for noise more easily and systematically.